Evaluation of endodontically treated teeth and related apical periodontitis using periapical and endodontic status scale: Retrospective cone-beam computed tomography study - Cikman, Ahter Sanal; Kose, Taha Emre; Gunacar, Dilara Nil; Cene, Erhan; Aricioglu, Banu (WILEY, 2022)
The purpose of this study was to evaluate the technical treatment quality and the status of apical pathology of endodontically treated teeth, as well as apical periodontitis (AP) prevalence, in a Turkish population using cone-beam computed tomography (CBCT). The CBCT images obtained between January 2018 and April 2020 were retrospectively examined. The quality of the endodontic treatments and the related periapical inflammatory lesions were classified according to the periapical and endodontic status scale (PESS). The data were statistically analysed using logistic regression, crosstabs and chi-square tests. AP was detected in 41% of 429 endodontically treated teeth. The prevalence of AP was significantly higher in teeth with inadequate root canal treatment compared with those with adequate treatment, 70.8% and 29.3%, respectively. Inadequate canal length and homogeneity, and complications were significantly associated with the prognostic periapical status scores of higher risk.
Keywords: apical periodontitis; cone-beam computed tomography; endodontically treated teeth; Periapical and Endodontic Status Scale; ROOT-CANAL TREATMENT; FILLED TEETH; PART 2; PREVALENCE; QUALITY; LESIONS; SUBPOPULATION; RADIOGRAPHY; FREQUENCY; Dentistry, Oral Surgery & Medicine